Call for Manuscripts Issue 3 - Crag Hill; Steven Bickmore; Leilya Pitre (University of Oklahoma Libraries, 2016)
Study and Scrutiny: Research in Young Adult Literature, a peer-reviewed journal, invites empirical research studies, critical/theoretical essays, and interviews with authors for its third issue. Edited by Crag Hill, Leilya Pitre, and Steve Bickmore, Study and Scrutiny is an open access journal published twice a year hosted by the University of Oklahoma.